Teori Belajar Konstruktivisme Dengan Model Pembelajaran (Inquiry) - Mulyadi, Mulyadi (Konsorsium Dosen Sekolah Tinggi Agama Islam (STAI) Al-Yasini Pasuruan, 2022)
The theory of constructivism learning is the application of learning whose application to the response to the development of new expectations is related to the learning process that wants the active role of students in building thinking patterns and initiating their own learning activities, This research approach uses as a conceptual approach, As a unitary research of science, the source of the data comes from primary data. Primary data are obtained through tracing original sources written by figures, and assisted by tracing secondary sources in the form of references from tertiary sources, constructive learning theory, in the concept of constructivism learning theory students play an active role in building their thinking patterns in understanding the teaching material provided by educators, therefore this theory of constructivism is very possible when used in class in carrying out learning using learning model that is in accordance with the needs of the implementation